2019
DOI: 10.1111/fcp.12490
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant effect of melatonin through ATP‐sensitive channels in mice

Abstract: Melatonin is a neurohormone secreted principally by the pineal gland. This molecule has various pharmacological properties including improving immune system, prevent cancer, anti‐aging, and anti‐oxidant effects. The anticonvulsant effects of melatonin have been proved by previous studies. Adenosine triphosphate (ATP)‐sensitive potassium (KATP) channels are considered as an important target in the seizure modulation. The aim of the present study was to investigate the anticonvulsant effect of melatonin in penty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…77 In further support, studies have also suggested that melatonin may enhance the antiseizure effects of morphine through the NO pathway. 78,79 A study conducted in 2020 showed that the anticonvulsant effect of melatonin may also be achieved by increasing the opening of the potassium (K ATP ) channels 80 (Table 1). Potassium channels such as Kir6.1 and Kir6.2 channels have been shown to be involved in the oxidative stress and mitochondrial dysfunction of epilepsy, and thus its relationship with melatonin should be investigated further.…”
mentioning
confidence: 99%
“…77 In further support, studies have also suggested that melatonin may enhance the antiseizure effects of morphine through the NO pathway. 78,79 A study conducted in 2020 showed that the anticonvulsant effect of melatonin may also be achieved by increasing the opening of the potassium (K ATP ) channels 80 (Table 1). Potassium channels such as Kir6.1 and Kir6.2 channels have been shown to be involved in the oxidative stress and mitochondrial dysfunction of epilepsy, and thus its relationship with melatonin should be investigated further.…”
mentioning
confidence: 99%
“…Clinical and experimental data in several animal models, including the temporal lobe epilepsy model, confi rm the anticonvulsant role of the pineal hormone melatonin [18]. Its advantages are good safety profi le (being an endogenous compound), potent antioxidant activity, contribution to degeneration protection of neurons against the mutagenic and carcinogenic eff ect of oxidants, and above all, its essential biological function to synchronize natural rhythms.…”
Section: Discussionmentioning
confidence: 98%
“…Melatonin may exert the anticonvulsant effect by GABA receptor modulation (Gunata et al 2020;Wan et al 1999), closure of the voltage-dependent calcium channel (Choi et al 2014), suppression of glutamatergic transmission in the striatum (Escames et al 2004), increasing the opening of K ATP channels (Mohammadi et al 2020), and by attenuation of hippocampal and cerebral cortex hyperexcitability through MT 1 receptor agonism (Ray et al 2004). Melatonin and its metabolites directly scavenge various free radicals in a receptor-independent manner and also stimulate the activity of several antioxidant enzymes and inhibit activities of oxidative enzymes (Reiter et al, 2007(Reiter et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…2004), increasing the opening of K ATP channels (Mohammadi et al. 2020), and by attenuation of hippocampal and cerebral cortex hyperexcitability through MT 1 receptor agonism (Ray et al. 2004).…”
Section: Discussionmentioning
confidence: 99%